How plants inspire façades. From plants to architecture: Biomimetic principles for the development of adaptive architectural envelopes. (January 2017) - López, Marlén; Rubio, Ramón; Martín, Santiago; Ben Croxford
Abstract: Façades have an important role in the control of energy waste in buildings, nevertheless most of them are designed to provide static design solutions, wasting large amounts of energy to maintain the internal comfort. However, biological adaptation solutions are complex, multi-functional and highly responsive. This paper proposes a biomimetic research of the relationship that can be developed between Biology and Architecture in order to propose innovative façade design solutions. We focus on plants, because of plants, like buildings, lack of movement and remain subject to a specific location. Nevertheless, plants have adapted to the environment developing special means of interaction with changing external issues. This paper provides a methodology to create a data collection of plant adaptations and a design mapping to guide the transfer from biological principles to architectural resources, as well as two design concept cases, opening new perspectives for new possible technical solutions and showing the potential of plant adaptations to environmental conditions at a specific climate. Further step is the transformation of some design concepts into technical solutions through experiments with new technologies that include multi-material 3D printing or advances in material science. Highlights: From plant adaptations to adaptive architectural envelopes using biomimicry. Adaptive envelopes that change with time to adapt environmental conditions. Techniques abstracted from plants that respond to different environmental issues. Climate and environmental issues that act as green triggers. Design concept generation with dynamic mechanisms and static strategies.